Adapting A Project-Based Aging Laboratory During a Pandemic. (17th December 2021) - Andersen, Troy; Edelman, Linda
Abstract: Aging Well in Utah is a competitive 2-semester project-based Honor's College Praxis Laboratory for 9 students from different degree programs dedicated to deepening understanding of the aging process through a broad gerontological lens. This session will address how the course was adapted during the COVID-19 pandemic, including: 1) scheduling virtual class times with guest lecturers; 2) conducting older adult interviews via Zoom to provide students experience in communicating "what matters most", one of the 4Ms of Age Friendly HealthCare; 3) adapting a student-designed medical narrative project highlighting stories of transition and healing through the dying process for previously unsheltered residents of a hospice program to focus on the lived experience of hospice patients during COVID-19; and 4) utilizing virtual technology to interview hospice patients, family members and hospice staff. In spite of challenges, student evaluations were above average and reported increased interest in incorporating age-friendly concepts into future careers.